Environmental and Metabolic Sensors That Control T Cell Biology - Ramsay, George; Cantrell, Doreen (Frontiers in Immunology, 2015)
The T lymphocyte response to pathogens is shaped by the microenvironment. Environmental sensors in T cells include the nutrient sensing serine/threonine kinases AMPK (adenosine monophosphate-activated protein kinase) and mTORc1 (mammalian target of rapamycin complex 1). Other environmental sensors are transcription factors such as HIF-1 (hypoxia-inducible factor-1) and the Aryl Hydrocarbon Receptor. The present review explores the molecular basis for the impact of environmental signals on the differentiation of conventional TCRαβ T cells and how the T cell response to immune stimuli can co-ordinate the T cell response to environmental cues.